Metal catalyst free cyclization of 3-alkynyl substituted 2-(indol-3-yl)quinoxalines in TFA alone: a new synthesis of indolophenazines. Issue 1 (30th November 2016) - Kumar, K. Shiva; Bhaskar, Boyapally; Ramulu, Meesa Siddi; Kumar, N. Praveen; Ashfaq, Mohd Ashraf; Pal, Manojit
Abstract : A new synthesis of indolophenazines has been achieved via cyclization of 3-alkynyl substituted 2-(indol-3-yl)quinoxalines in TFA alone. Abstract : TFA alone was found to be remarkably effective for the intramolecular hydroarylation (IMHA) of alkynes when employed as a solvent in the cyclization of 3-alkynyl substituted 2-(indol-3-yl)quinoxalines. This simple and metal free cyclization method afforded a range of indolophenazines as new and potential cytotoxic agents. The use of excess TFA was found to be crucial for the success of this reaction.